1986
DOI: 10.3109/00365548609032330
|View full text |Cite
|
Sign up to set email alerts
|

Erythema Chronicum Migrans in Sweden: Clinical Manifestations and Antibodies to Ixodes ricinus Spirochete Measured by Indirect Immunofluorescence and Enzyme-linked Immunosorbent Assay

Abstract: 26 Swedish patients with erythema chronicum migrans (ECM) were studied regarding associated clinical symptoms and antibodies to Swedish Ixodes ricinus spirochete. 11/26 (42%) of the patients had associated symptoms, compared to more than 90% of 314 American patients with ECM, as described by Steere et al. Only 2/26 (8%) had multiple skin lesions, compared to 48% of the American patients. Elevated erythrocyte sedimentation rate and circulating immune complexes were demonstrated in 6/25 (24%) and 8/25 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The low sensitivity of the Diagast HA in both early and late Lyme borreliosis (8 % and 62 %) and the relatively low sensitivity of the IFAs in early Lyme borreliosis compared to the EIAs (31% versus ~ 46 %), is in agreement with the findings of others (19,(21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 90%
“…The low sensitivity of the Diagast HA in both early and late Lyme borreliosis (8 % and 62 %) and the relatively low sensitivity of the IFAs in early Lyme borreliosis compared to the EIAs (31% versus ~ 46 %), is in agreement with the findings of others (19,(21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 90%
“…Serological studies have shown seropositivity rates of 25 to 50% in patients with EM and 50 to 80% in patients with neuroborreliosis (9,10,14,21,22). The diagnostic sensitivity of ELISA has been increased by the introduction of new antigens, e.g., the flagellum antigen (10,14), and capture ELISA instead of indirect ELISA for the immunoglobulin M (IgM) analysis (12).…”
mentioning
confidence: 99%
“…It should immediately be confirmed by determination of antibodies against B. burgdorferi (6)(7)(8)(9). In atypical patients serology is essential, with the reservation that a positive titer to B. burgdorferi may represent a "serologic scar" due to a previous infection without actual interest.…”
mentioning
confidence: 99%